Spontaneous pneumoperitoneum in pediatric patients: Dilemmas in Management - Rahul Gupta (Wolters Kluwer Medknow Publications, 2018)
Context: Pneumoperitoneum is typically a surgical emergency, particularly in neonates. However, pneumoperitoneum can rarely present without gastrointestinal perforation which is known as spontaneous pneumoperitoneum. Aims: This study aims to analyze the outcome of pediatric patients with spontaneous pneumoperitoneum and describe our experience. Settings and Design: A retrospective study performed from January 2014 to May 2017. Materials and Methods: The study included all pediatric patients admitted in a tertiary care institute. Results: There were 9 patients with 5 males and 4 females, out of which 7 were neonates. At presentation, respiratory distress was a common complaint (8/9). 5 out of all patients developed abdominal distension. Associated malformations were seen in 5 patients. Pneumoperitoneum was preceded by mechanical ventilation in 5 patients. Abdominal examination revealed soft distension with relaxed abdominal wall in 7, while marked distension was present in 2 cases. Features suggestive of peritonitis were absent in all the patients. Abdominal radiographs revealed free air in all, while, radiographic evidence of pneumothorax was seen in 2 patients. Conservative management without any operative intervention was performed in 3 patients with favorable outcome. Laparotomy was performed in 1 patient; negative for any perforation and outcome was unfavorable. In 5 patients, abdominocentesis was performed followed by abdominal drain placement. No patient had any evidence of leakage of intestinal contents from gastrointestinal tract after insertion of abdominal drain. Favorable outcome was present in 5 patients. Out of 4 cases with unfavorable outcome, 3 patients were having esophageal atresia. Conclusions: A high index of suspicion for spontaneous pneumoperitoneum must be present when dealing with pediatric patients, especially neonates with pneumoperitoneum and without clinical signs of peritonitis. A comprehensive clinical evaluation with sepsis screen must be carried out to supplement the diagnosis. Pneumoperitoneum in pediatric patients, especially neonates, is not always an absolute indication for surgery.